phiC31 Integrase-Mediated Site-Specific Recombination in Barley - Kapusi, Eszter (Public Library of Science, 2012)
The Streptomyces phage phiC31 integrase was tested for its feasibility in excising transgenes from the barley genome through site-specific recombination. We produced transgenic barley plants expressing an active phiC31 integrase and crossed them with transgenic barley plants carrying a target locus for recombination. The target sequence involves a reporter gene encoding green fluorescent protein (GFP), which is flanked by the attB and attP recognition sites for the phiC31 integrase. This sequence disruptively separates a gusA coding sequence from an upstream rice actin promoter. We succeeded in producing site-specific recombination events in the hybrid progeny of 11 independent barley plants carrying the above target sequence after crossing with plants carrying a phiC31 expression cassette. Some of the hybrids displayed fully executed recombination. Excision of the GFP gene fostered activation of the gusA gene, as visualized in tissue of hybrid plants by histochemical staining. The recombinant loci were detected in progeny of selfed F(1), even in individuals lacking the phiC31 transgene, which provides evidence of stability and generative transmission of the recombination events. In several plants that displayed incomplete recombination, extrachromosomal excision circles were identified. Besides the technical advance achieved in this study, the generated phiC31 integrase-expressing barley plants provide foundational stock material for use in future approaches to barley genetic improvement, such as the production of marker-free transgenic plants or switching transgene activity.